2013
DOI: 10.2174/1874325001307010152
|View full text |Cite
|
Sign up to set email alerts
|

Functionality and Safety of an Ultra-Congruent Rotating Platform Knee Prosthesis at 5.6 Years: More than 5- Year Follow-Up of the e.motion® UC-TKA

Abstract: Background:Mobile bearing TKA prostheses were designed to minimize polyethylene wear by increasing implant conformity and reducing stresses between the articulating prosthesis components. It is the purpose of this study to assess the mid-term functionality and clinical outcome associated with a highly congruent mobile platform design, the e.motion® UC total knee prosthesis.Material and Methods:Functional and clinical outcomes were assessed after an average of 5.6 years (5.1 – 6.0 years) after total knee arthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…Nonetheless, no notable differences were found for any type of adverse events between the two groups. Our finding is in accordance with previous studies reporting no increased incidence of adverse events with the e.motion-UC [38][39][40]. Our findings lead us to believe that the mobile-bearing UC prosthesis is a reasonably safe alternative to the mobile-bearing PS prosthesis when precise and meticulous surgical techniques are exercised.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Nonetheless, no notable differences were found for any type of adverse events between the two groups. Our finding is in accordance with previous studies reporting no increased incidence of adverse events with the e.motion-UC [38][39][40]. Our findings lead us to believe that the mobile-bearing UC prosthesis is a reasonably safe alternative to the mobile-bearing PS prosthesis when precise and meticulous surgical techniques are exercised.…”
Section: Discussionsupporting
confidence: 93%
“…This interesting finding is in agreement with previous studies reporting only a weak correlation between the postoperative maximum flexion and the clinical parameters for pain relief, joint function, and quality of life [41,42]. This study, along with previous midterm studies of TKAs performed with the e.motion-UC [38][39][40], indicates that the mobile-bearing UC prosthesis provides satisfactory functional outcomes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite the regular use of these UC inserts, there is only limited evidence about mid- or long-term outcome. Only few studies report 5- or 10-year results, none with an appropriate control group [ 3 , 10 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike fixed‐bearing systems, mobile‐bearing systems can theoretically reduce bearing wear by decreasing the stresses between the component and the polyethylene and decrease implant loosening by spreading the load to the soft tissue [5, 11]. However, few clinical studies to date have looked at this higher‐conformity design regardless of bearing type [16, 18], and only a few comparison studies of mobile and fixed UC designs have been reported [6, 15]. The purpose of this study was to retrospectively compare clinical and radiological outcomes as well as survival rates of the Columbus ® and e.motion UC knee systems after a minimum follow‐up period of 5 years.…”
Section: Introductionmentioning
confidence: 99%